GAMBARAN KARAKTERISTIK KASUS KEKERASAN SEKSUAL YANG DIPERIKSA DI RS BHAYANGKARA TINGKAT II MEDAN PADA TAHUN 2020-2021 - LISA HANDAYANI; MISTAR RITONGA; ABDUL GAFAR PARINDURI; HASRONI FATHURRAHMAN (LP2MTBM MAKARIOZ, 2023)
Violence is very common in everyday life, both in the family, the community, and among peers. Violence or in English, violence, can beinterpreted as an attack or invasion of a person's physical or mental integration. Generally, to know the Characteristicsof sexual violence cases examined at the Hospital Bhayangkara Tk. II Medan in 2020–2021. Research that takes databased on the results of medical records, research design is in the form of descriptive with a restospective approach to findout how the characteristics of sexual violence cases are examined in hospitals. Bhayangkara Tk. II Medan in 2020–2021.The results of study show the frequency distribution based on age of those who experienced sexual violence in Bhayangkara TK II HospitalMedan the most were early teens, as many as 160 people (55.7%). The frequency distribution based on gender.experienced sexual violence at Bhayangkara TK II Hospital Medan was mostly female, as many as 282 people (98.3%) and 5people (1.7%). The frequency distribution based on the year of occurrence of sexual violence in Bhayangkara TK II MedanHospital was the highest in 2020, with as many as 145 people (50.5%), based on gender, who experienced sexual violence atAt Bhayangkara TK II Hospital Medan, the majority were women, as many as 282 people. (98.3%). While the frequency based onthe type of wound that experienced sexual violence in Bhayangkara TK II Hospital Medan the most were torn wounds asmany as 263 people (91.6%).